Administration of prostacyclin modulates cutaneous blood flow but not sweating in young and older males: roles for nitric oxide and calcium‐activated potassium channels. (23rd September 2016) - Fujii, Naoto; Notley, Sean R.; Minson, Christopher T.; Kenny, Glen P.
Abstract : Key points: In young adults, cyclooxygenase (COX) contributes to the heat loss responses of cutaneous vasodilatation and sweating, and this may be mediated by prostacyclin‐induced activation of nitric oxide synthase (NOS) and calcium‐activated potassium (KCa) channels. This prostacyclin‐induced response may be diminished in older relative to young adults because ageing is known to attenuate COX‐dependent heat loss responses. We observed that, although prostacyclin does not mediate sweating in young and older males, it does modulate cutaneous vasodilatation, although the magnitude of increase is similar between groups. We also found that, although NOS and KCa channels contribute to prostacyclin‐induced cutaneous vasodilatation in young males, these contributions are diminished in older males. Our findings provide new insight into the mechanisms governing heat loss responses and suggest that the age‐related diminished COX‐dependent heat loss responses reported in previous studies may be a result of the reduced COX‐derived production of prostanoids (e.g., prostacyclin) rather than the decreased sensitivity of prostanoid receptors. Abstract: Cyclooxygenase (COX) contributes to the regulation of cutaneous vasodilatation and sweating; however, the mechanism(s) underpinning this response remain unresolved. We hypothesized that prostacyclin (a COX‐derived product) may directly mediate cutaneous vasodilatation and sweating through nitric oxide synthase (NOS) and calcium‐activated potassium (KCa) channels in young adults. However, these responses would be diminished in older adults because ageing attenuates COX‐dependent cutaneous vasodilatation and sweating. In young (25 ± 4 years) and older (60 ± 6 years) males (nine per group), cutaneous vascular conductance (CVC) and sweat rate were evaluated at four intradermal forearm skin sites: (i) control; (ii) 10 mm N G ‐nitro‐l ‐arginine (l ‐NNA), a non‐specific NOS inhibitor; (iii) 50 mm tetraethylammonium (TEA), a non‐specific KCa channel blocker; and (iv) 10 mm l ‐NNA + 50 mm TEA. All four sites were coadministered with prostacyclin in an incremental manner (0.04, 0.4, 4, 40 and 400 μm each for 25 min). Prostacyclin‐induced increases in CVC were similar between groups (all concentrations, P  > 0.05).l ‐NNA and TEA, as well as their combination, lowered CVC in young males at all prostacyclin concentrations ( P  ≤ 0.05), with the exception ofl ‐NNA at 0.04 μm ( P  > 0.05). In older males, CVC during prostacyclin administration was not influenced byl ‐NNA (all concentrations), TEA (4‐400 μm ) or their combination (400 μm ) ( P  > 0.05). No effect on sweat rate was observed in either group (all concentrations, P  > 0.05). We conclude that, although prostacyclin does not mediate sweating, it modulates cutaneous vasodilatation to a similar extent in young and older males. Furthermore, although NOS and KCa channels contribute to the prostacyclin‐induced cutaneous vasodilatation in young males, these contributions are diminished in older males. Key points: In young adults, cyclooxygenase (COX) contributes to the heat loss responses of cutaneous vasodilatation and sweating, and this may be mediated by prostacyclin‐induced activation of nitric oxide synthase (NOS) and calcium‐activated potassium (KCa) channels. This prostacyclin‐induced response may be diminished in older relative to young adults because ageing is known to attenuate COX‐dependent heat loss responses. We observed that, although prostacyclin does not mediate sweating in young and older males, it does modulate cutaneous vasodilatation, although the magnitude of increase is similar between groups. We also found that, although NOS and KCa channels contribute to prostacyclin‐induced cutaneous vasodilatation in young males, these contributions are diminished in older males. Our findings provide new insight into the mechanisms governing heat loss responses and suggest that the age‐related diminished COX‐dependent heat loss responses reported in previous studies may be a result of the reduced COX‐derived production of prostanoids (e.g., prostacyclin) rather than the decreased sensitivity of prostanoid receptors.